Sosialisasi Senam Hamil Yoga untuk Mengurangi Ketidaknyamanan pada Kehamilan Trimester III di Puskesmas Kebon Kopi - Gustina Gustina; Nurbaiti Nurbaiti (Jurnal Abdimas ADPI Sains dan Teknologi, 2022)
One of the midwifery care that can be done as a quality approach is physical exercise, such as meditation/yoga. Pregnancy yoga exercise at this time is one of the self-help solutions that support the process of pregnancy, birth and even child care that can be done in antenatal care classes. (Ministry of Health, 2010). Prenatal care yoga during pregnancy can increase birth weight and reduce the incidence of preterm and delivery complications according to Narendran (2009) from the Vivekananda Yoga Research Foundation in Bangalore. In addition, a study showed that yoga and meditation can reduce psychological stress and physical injury during pregnancy and childbirth, including anxiety and pain (Amy E. B, et al, 2009). This activity aims to increase the knowledge of mothers to overcome the discomfort of the third trimester of pregnancy. Due to the Covid-19 Pandemic, we were unable to collect mothers, so the implementation method was carried out by providing leaflets through Independent Practice Midwives (BPM) in the working area of ​​Pustu Pasir Putih. The results obtained were 33 visits by pregnant women in the third trimester, 26 people did not know and 7 people knew about prenatal care yoga and all pregnant women were given leaflets to increase knowledge about prenatal care yoga in an effort to reduce discomfort in the third trimester of pregnancy.